MRI in Acute Non-Accidental Head Injury - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
The value of magnetic resonance imaging (MRI) in the diagnosis of acute non-accidental head injury (NAHI) was studied retrospectively in 12 infants and children, ages 1 to 34 months (average, 5.7 months), admitted to the Royal Hospital for Sick Children, Edinburgh, Scotland.